Anthropometry, food and body self-image of women gym member in Caxias do Sul -RS - Ferreira, Kamila Petry (2012)
The nutrition transition is characterized by change of diet "traditional" by "occidental" diet, changing the profile "thin" to a significant increase in obesity. In Brazil, it affected the behavior and vision for the physical form of women, including aspects of food, physical and aesthetic. The aim of this study was to investigate the relationship between body image and nutritional status of adult women attending a gym academy of Caxias do Sul -RS. It was evaluated: body mass index (BMI), by height and weight; the percentage of body fat by skin fold catching and calculating the percentage of body fat; the intake, through the 24-hour recall; the perception of body image using a validated questionnaire about body image; and physical exercises, using a questionnaire with closed questions. Results: It was found as following results: the mean BMI was 24,13kg/m²; 57.14% would like to have one to two profiles lower than the actual profile; 28.57% were dissatisfied with the current contour would like a silhouette or greater than the current (14.29%). Compared with BMI scores in the silhouettes, the data indicated that high BMI's are linked to scores of silhouettes too high (or the opposite, with low BMI are related to low scores for silhouettes). Conclusion: The women in this study were well nourished and didn’t eat more then the recommended intake calories, however, most were dissatisfied with the current fitness and not bother to get a more healthy through exercise